Effects of psychotropic switches on weight change: a prospective cohort study. (1st June 2022) - Piras, M.; Ranjbar, S.; Dubath, C.; Laaboub, N.; Grosu, C.; Gamma, F.; Von Plessen, K.; Von Gunten, A.; Conus, P.; Eap, C.
Abstract : Introduction: Many psychotropic drugs can induce weight gain with differences in their metabolic risk profiles (i.e. high, medium or low-risk). Objectives: To compare the weight evolution of patients switching versus patients keeping their psychotropic drugs with different risk-profiles. Methods: Data for patients switching or keeping the same drug were obtained from the Psyclin (from 2007 to 2015) and Psymetab (2007- 2019) cohort studies, conducted at the Lausanne University Hospital, Switzerland. Patients either switched from a high to a low-risk, a high to a medium-risk, a medium to a low-risk drug, or for a drug with the same risk category. Patients not switching either kept a high, medium or low-risk drug. The evolution of weight is currently being analyzed using a linear mixed-effect model. Results: Preliminary results showed that switching from a high to low-risk molecule had the strongest impact on weight changes. The analysis being ongoing, the quantitative results will be presented at the congress. Conclusions: Switching from a high-risk to a low-risk molecule is likely to have the strongest impact on weight changes. Disclosure: No significant relationships.